Pengujian Flavonoid Total Dan Uji Aktivitas Antioksidan Fraksi Aktif Daun Akar Kaik-Kaik (Uncaria cordata (Lour.) Merr) Yang Berpotensi Sebagai Obat Diare - Silvia Deswita Silvia; Eva Nadia Rahma; Violica Celloce Njurumana; Rini Yanuarti (Jurnal Biologi dan Pembelajarannya (JB&P), 2022)
kar kaik-kaik (Uncaria cordata (Lour.) Merr.) is a medicinal plant used forgenerations by the Dayak tribe to treat diarrhea and dysentery. This study aimsto determine the total flavonoid content and antioxidant activity of the activefraction of kaik-kaik root leaves which have the potential to cure diarrhea. Kaikkaik root leaf extract was made by maceration using 70% ethanol. Totalflavonoid test was carried out using UV-VIS spectrophotometry with quercetinstandard. The results showed that the ethanol fraction had the highest flavonoidcontent, namely9.08 mg QE/g sample,n-hexane fraction of 5.21mg QE/gsample and ethyl acetate fraction of 3.54 mg QE/g. Testing of antioxidantactivity using the DPPH method. The results showed that the ethanol fractionhad a very strong antioxidant activity of 49.22 ppm, the n-hexane fraction had amoderate antioxidant activity of 108.22 ppm and the ethyl acetate fraction had amoderate antioxidant activity of 130.30. The total flavonoid content andantioxidant activity of the kaik-kaik root leaf extract indicate that the kaik-kaikroot leaf extract has the potential to be developed into herbal medicine to treatdiarrhea.